Case report of fatal Mycobacterium tilburgii infection. Issue 7 (July 2015) - Akpinar, Timur; Bakkaloglu, Oguz K.; Ince, Burak; Tufan, Fatih; Kose, Murat; Poda, Mehves; Tascioglu, Didem; Koksalan, O. Kaya; Saka, Bulent; Erten, Nilgun; Buyukbabani, Nesimi; Kilicaslan, Zeki; et al.
Abstract: There are few reports concerning Mycobacterium tilburgii infection in humans because this bacterium is non-cultivatable. Herein, using new molecular techniques, we report the case of an immunocompromised patient with fatal disseminated lymphadenitis that was caused by M. tilburgii .26 years old Caucasian HIV negative female patient presented with abdominal pain. Her clinical assessment revealed disseminated lymphadenitis, that was acid fast bacilli positive. Further molecular evaluation showed the causative agent as M. tilburgii . Despite anti mycobacterial therapy and careful management of intervening complications patient died because of an intraabdominal sepsis. This is the first fatal M. tilburgii infection in the literature. This case points the importance of careful management of patient's immune status and intervening infections besides implementation of effective drug treatment.